EFFECTS OF BLENDING RICE BRAN OIL BIODIESEL with diesel ON THE PROPERTIES OF - Bello, Emmanuel I.; Oluboba, Oluwole (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Some properties of rice bran oil and the biodiesel such as saponification value and iodine value even when within standard limits can be more effective if reduced further. One way of achieving this is to blend with diesel. Rice bran oil was extracted using a soxhlet extractor operated at 60oC. The oil was transesterified directly using methanol and sodium hydroxide without pretreatment with an acid as the free fatty acid content was low at 0.12% oleic acid. The biodiesel produced was used to blend diesel to 10% (B10) and 20% (B20). The oil, biodiesel and blends were characterized using the ASTM protocols and the results obtained shows that the densities and viscosities of the oil reduced after transesterification and blending, while flash points and cetane number of the samples increased. Most of the properties after blending are within the limits of ASTM D6751-02 standards for biodiesel thus allowing them to be used as alternative fuels for diesel engines.